دراسة نقدية تحليلية في كتاب المُوشَّح للمَرْزُبَـاني - بن دومة, كرفـاوي; زهرة, عـزالدين (University of Eloued جامعة الوادي, 2018)
" اهتم كتاب الموشح برصد المآخذ والعيوب التي وقع فيها الشعراء العرب من القدماء والمحدثين، والتي شكلت صورة شبه متكاملة عن قضايا النقد العربي القديم". تحاول هذه الدراسة تتبع أهم المآخذ والعيوب الفنية التي وقف عندها المرزباني في مصنفه، وما أخذه العلماء على الشعراء من أخطاء لغوية وفنية.. منوها على ضرورة تجنب كل ما يخل بجماليات القول الشعري خاصة والإبداع الأدبي بصفة عامة The book of « El Mowashah » is concerned with monitoring the shortcomings and drawbacks that ancient and modern Arab poets have fallen into, and which formed an almost complete picture about the issues of ancient Arab criticism . This study attempts to follow the most important defects and technical shortcomings that Marzabani focused on in his work, and what the scientists caught from the poets language and technical errors .. Noting the need to avoid everything that prejudices the aesthetics of poetic and literary creativity in general.
Keywords: الموشح، المرزباني، النقد العربي القديم; El Mowashah, Marzabani, Ancient Arab Criticism